Tuning the net topology of a ternary Ag(i)-1, 2, 4, 5-tetra(4-pyridyl)benzene-carboxylate framework: structures and photoluminescence. Issue 42 (9th October 2019) - Liu, Wei; Chen, Cong-Cong; Mao, Ling-Ling; Wu, Si-Guo; Wang, Long-Fei; Tong, Ming-Liang
Abstract : Changing of auxiliary ligands leads to the formation of 1D–3D coordination structures and the use of dye molecules provides a way to promote the luminescence properties of MOFs. Abstract : The dye molecule 1, 2, 4, 5-tetra(4-pyridyl)benzene (bztpy), a tetradentate ligand, can be an excellent candidate for construction of coordination polymers with photoluminescence properties. Here, based on Ag(i ) and bztpy, three novel complexes, namely [Ag2 (bza)2 (μ4 -bztpy)] (1 ), [Ag2 (μ-ipa)(μ4 -bztpy)]·EtOH·3H2 O (2 ) and [Ag3 (pda)(μ-pda)1/2 (μ4 -bztpy)2 ]·3EtOH·6H2 O (3 ) (Hbza = benzoic acid, H2 ipa = isophthalic acid and H2 pda = 2, 4-pyridinedicarboxylic acid), have been synthesized with the assistance of auxiliary carboxylates. The choice of carboxylates was found to have a pronounced effect on the framework topology. Structural analysis revealed that there are [Ag2 (bztpy)]∞ chains as basic side groups and the change of interconnected auxiliary ligands from Hbza to H2 pda leads to the formation of 1D, 2D and 3D structures, respectively. They were further characterized by elemental analysis, IR, single-crystal X-ray diffraction and luminescence study.